2019
DOI: 10.21273/hortsci14205-19
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Anatomy of Apple Trees during Seasonal Periods under Subtropical Conditions

Abstract: Water deficits are considered the primary environmental stress in agriculture, and improving the growth and production of plants under this stress is one of the primary goals of breeding and crop management programs. The apple tree is a plant that is negatively affected by water stress. Plants that develop under a water deficit may develop physiological and anatomical strategies to survive or even produce fruits in these environments. In view of the importance of and lack of studies of the leaf anatomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…A thicker palisade tissue may have a role in increasing the number of CO 2 -fixation sites. A thicker spongy paraenchyma could result in easier diffusion of Co 2 to these sites, thus maintaining the photosynthesis rate of leaves under deficit water (ENNAJEH et al, 2010;LOCATELLI et al, 2019). The thickening of the vascular bundles of plant leaves allows for greater flows of water and mineral salts during the water deficit, thus adaptive it to water stress conditions (Queiroz-Voltan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thicker palisade tissue may have a role in increasing the number of CO 2 -fixation sites. A thicker spongy paraenchyma could result in easier diffusion of Co 2 to these sites, thus maintaining the photosynthesis rate of leaves under deficit water (ENNAJEH et al, 2010;LOCATELLI et al, 2019). The thickening of the vascular bundles of plant leaves allows for greater flows of water and mineral salts during the water deficit, thus adaptive it to water stress conditions (Queiroz-Voltan et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The thickening of the vascular bundles of plant leaves allows for greater flows of water and mineral salts during the water deficit, thus adaptive it to water stress conditions (Queiroz-Voltan et al 2014). On the other hand, Locatelli et al, (2019) reported that the xylem vessels of leaves were increased in number and were reduced in diameter under deficit water. Thus, it increases resistance to high pressures in the water column.…”
Section: Discussionmentioning
confidence: 99%
“…This information has great relevance for the selection of promising materials, as the higher stomatal frequency and density represent an important tolerance response to water deficit (I. Oliveira et al, 2018;Locatelli et al, 2019). It occurs because a higher stomatal density allows the stomatal opening in a period in which it is possible to capture CO 2 and prevents excessive transpiration.…”
Section: Estimates Of the Relative Contribution Of Anatomical And Vegetative Traits To Geneticmentioning
confidence: 99%
“…Leaf anatomy studies associated with vegetative traits provide support for the identification of promising genotypes, considering early selection and the use of selection indices that consider the combination of various characteristics as selection criteria, seeking to identify genotypes that present a set of favorable characteristics (Gama, Sales, Castanheira, Silveira, & Azevedo, 2017;Oliveira, Meyerb, Afonso, & Gonçalves, 2018;Viana et al, 2018a,b;Locatelli et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There are many factors affecting leaf chemical uptake dynamics, with relative humidity being one of them [17][18][19][20]. High relative humidity conditions can affect the leaf morphological structure, reducing the thickness of the parenchyma and both the adaxial and abaxial epidermis [30,31], leaving a softer and thinner (less waxy and more permeable) cuticle, which is more prone to chemical absorption. Previous observations [20] confirmed these aspects as a 50% increase of urea leaf absorption was observed after a relative humidity increase from 35% to 50%.…”
Section: Metamitron Absorptionmentioning
confidence: 99%